Positivisme(s), écoles et mouvances - Annie Petit (Revue d’Histoire des Sciences Humaines)
Comte founded his “positivist school” against “theological” or “ metaphysical” schools in philosophy and “retrograde”, “revolutionary” or “stationary” schools in politics. Education was a major issue. His disciples broke up into different currents. Some, following Émile Littré and the journal La Philosophie positive (1867-1883), adopted positive philosophy, while refusing some tenets of political and religious positivism. The so-called complete positivists, under the leadership of Pierre Laffitte, found an outlet in La Revue occidentale (1878-1914). Controversies and schisms arose. A new association, and yet another journal, Revue positiviste internationale (1906-1940) were established. In this complex history the dissidents defended a corrected doctrine, whereas the orthodox followers were divided between the development of a school as education or a school as church, and the political choices varied as well. Positivism as a school of thought, which is associated with a multiplicity of networks, is a protean and enduring label.